Diary of a wimpy kid cabin fever - Kinney, Jeff (Puffin London, 2013)
School property has been damaged and Greg is the prime suspect. The authorities are closing in, but then a surprise blizzard hits and the Heffley family is trapped indoors. Greg knows that when the snow melts he's going to have to face the music but could any punishment be worse than being stuck inside with your family for the holidays?